Early use of donepezil against psychosis and cognitive decline in Parkinson's disease: a randomised controlled trial for 2 years. Issue 12 (3rd August 2018) - Sawada, Hideyuki; Oeda, Tomoko; Kohsaka, Masayuki; Umemura, Atsushi; Tomita, Satoshi; Park, Kwiyoung; Mizoguchi, Kouichi; Matsuo, Hidenori; Hasegawa, Kazuko; Fujimura, Harutoshi; Sugiyama, Hiroshi; Nakamura, Michikazu; et al.
Abstract : Objectives: Brain acetylcholine is decreased even in patients with cognitively preserved Parkinson's disease (PD). We investigated whether early and long-term use of donepezil prevents psychosis in non-demented PD patients. Methods: A double-blinded, placebo-controlled trial was conducted. A total of 145 non-demented PD patients were randomly assigned to receive 5 mg/day donepezil (n=72) or placebo (n=73) for 96 weeks. Medications for PD were not restricted, but antipsychotic drugs were not permitted throughout the study. The primary outcome measure was survival time to psychosis that was predefined by Parkinson's Psychosis Questionnaire (PPQ) B score ≥2 or C score ≥2. Secondary outcome measures included psychosis developing within 48 weeks, total PPQ score, Mini-Mental State Examination (MMSE), Wechsler Memory Scale (WMS) and subgroup analysis by apolipoprotein ε4 genotyping. Results: Kaplan-Meier curves for psychosis development were very similar between the two groups, and the Cox proportional hazard model revealed an adjusted HR of 0.87 (95%CI 0.48 to 1.60). The changes in MMSE and WMS-1 (auditory memory) were significantly better with donepezil than in placebo. In the subgroup analysis, donepezil provided an HR of 0.31 (0.11–0.86) against psychosis in 48 weeks for apolipoprotein ε4 non-carriers. Conclusions: Although donepezil provided beneficial effects on PPQ, MMSE and auditory WMS score changes in 2 years, it had no prophylactic effect on development of psychosis in PD. Apolipoprotein ε4 may suppress the antipsychotic effect of donepezil. Trial registration number: UMIN000005403.